A framework of a sustainable performance measurements (SPMs) model for the Malaysian electronic and electrical industry - Teh, Boon Heng; Chong, Lee Lee; Yeap, Peik Foong; Ong, Tze San (IDOSI Publications, 2012)
This conceptual paper is initiated by the growing awareness of environmental and social responsibility issues. Companies’ excellent performance is no longer championed solely on financial matters but has expanded to environment and social perspectives, calling for the need for a sustainable performance measurements (SPMs) model. Frequent and in-depth sustainable reporting are expected to be more demanding and comprehensive in the future with an intense pressure on and expectation of various stakeholders. The adoption of sustainable performance reporting is already in place in developed countries such as Europe, the United States (US) and the United Kingdom(UK), but reporting is relatively low among developing nations especially countries from Asia; Malaysia is no exception. This is due to the fact that sustainability performance reporting in Malaysia is still in its infancy phase and is subject to plenty of uncertain issues particularly on SPMs models that need to be managed, measured and reported on. The SPMs model is developed to be applied in the Malaysian electronic and electrical industry as this industry is subjected to intense scrutiny from Western Nations in term of environmental and social compliance. This paper, therefore, aims to mitigate the problem by constructing a framework of SPMs models in order to promote genuine sustainable reporting among the industry.